(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This paper examines the pervasiveness of metaphorical constructions in day-to-day variety of language. It claims, in accordance with Lakoff and Johnson (1980), that the metaphorical expressions are not mere words, but they are part and parcel of our everyday speech and the way we conceptualize things and that metaphor is not restricted to poetic language or the literary style. The examples we give here are used to show that we use existing physical concepts to conceptualize these abstract concepts. يسلط هذا البحث الضوء على وفرة وجود عبارات الاستعارة في حديثنا اليومي. و استناداً إلى جورج لايكوف و مارك جونسن ( 1980) ندعي أن تعابير الاستعارة ليست قضية متعلقة بالكلمات و حسب بل هي جزء لا يتجزأ من الطريقة التي نعي بها الأشياء و نعقلها و أن الاستعارة ليست حكراً على اللغة الشعرية أو الأدبية. و نعطي أمثلة كثيرة لكي ندلل على أننا نستخدم القضايا المادية المحسوسة المتوفرة لدينا لكي نعي و نعقل الأفكار المجردة.